Enjoying Funny Ways for Learning English Language Skills: An Overview - Ghafar, Zanyar (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
For some individuals, the process of learning English may seem complex. Within academic settings, students continue to encounter challenges while acquiring proficiency in the English language. Teachers, as educators, should demonstrate ingenuity in selecting the optimal approach to language instruction. Utilizing learning tactics that are less enjoyable or potentially tedious does not enhance students' English proficiency; rather, it just induces feelings of boredom and lethargy, discouraging their motivation to study. The key aspect is that students get pleasure from each learning endeavor as an enjoyable experience. It might enhance the pupils' sense of comfort throughout the learning process. Engaging educational activities will effectively enhance pupils' English proficiency in a natural manner. It aids pupils in alleviating stress while studying. Hence, the methods of instruction should be meticulously crafted and tailored to meet the specific requirements of the pupils. The piece of writing focuses on the researcher’s viewpoint about enjoyable methods for acquiring English language skills. This article outlines some enjoyable methods for acquiring proficiency in the English language. The pupils might get pleasure from studying English.